The mechanism of the nucleo-sugar selection by multi-subunit RNA polymerases - Mäkinen Janne J; Shin Yeonoh; Vieras Eeva; Virta Pasi; Metsä-Ketelä Mikko; Murakami Katsuhiko S; Belogurov Georgiy A (NATURE RESEARCH, 2022)
RNA polymerases (RNAPs) synthesize RNA from NTPs, whereas DNA polymerases synthesize DNA from 2dNTPs. DNA polymerases select against NTPs by using steric gates to exclude the 2 ' OH, but RNAPs have to employ alternative selection strategies. In single-subunit RNAPs, a conserved Tyr residue discriminates against 2 ' dNTPs, whereas selectivity mechanisms of multi-subunit RNAPs remain hitherto unknown. Here, we show that a conserved Arg residue uses a two-pronged strategy to select against 2 ' dNTPs in multi-subunit RNAPs. The conserved Arg interacts with the 2 ' OH group to promote NTP binding, but selectively inhibits incorporation of 2 ' dNTPs by interacting with their 3 ' OH group to favor the catalytically-inert 2 ' -endo conformation of the deoxyribose moiety. This deformative action is an elegant example of an active selection against a substrate that is a substructure of the correct substrate. Our findings provide important insights into the evolutionary origins of biopolymers and the design of selective inhibitors of viral RNAPs. RNA and DNA polymerases need to discriminate efficiently against closely related nucleotide triphosphate substrates. Here, the authors show that a conserved Arg residue is the major determinant of selectivity against deoxyribonucleoside substrates by multisubunit RNA polymerases.